2003
DOI: 10.1016/s0093-934x(02)00506-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging of tongue-twister sentence comprehension: Twisting the tongue and the brain

Abstract: This study used fMRI to investigate the neural basis of the tongue-twister effect in a sentence comprehension task. Participants silently read sentences equated for the syntactic structure and the lexical frequency of the constituent words, but differing in the proportion of words that shared similar initial phonemes. The manipulation affected not only the reading times and comprehension performance, but also the amount of activation seen in a number of language-related cortical areas. The effect was not restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 52 publications
1
35
2
Order By: Relevance
“…The region we found in the present study is slightly inferior to the part of the insula reported in Dronkers (1996). In a recent fMRI study, the insula was among the regions that showed increased activity for "tongue-twister" sentences, even though the task was reading comprehension and did not involve articulation (Keller, Carpenter, & Just, 2003). We believe the involvement of this region in deficits in the linguistic domain in our experiment is most likely due to a recoding of read material into phonological and/or articulatory representations (e.g., Coltheart et al, 1993;Plaut et al, 1996).…”
Section: Lesion Correlates Of Impairments In the Linguistic Domaincontrasting
confidence: 78%
“…The region we found in the present study is slightly inferior to the part of the insula reported in Dronkers (1996). In a recent fMRI study, the insula was among the regions that showed increased activity for "tongue-twister" sentences, even though the task was reading comprehension and did not involve articulation (Keller, Carpenter, & Just, 2003). We believe the involvement of this region in deficits in the linguistic domain in our experiment is most likely due to a recoding of read material into phonological and/or articulatory representations (e.g., Coltheart et al, 1993;Plaut et al, 1996).…”
Section: Lesion Correlates Of Impairments In the Linguistic Domaincontrasting
confidence: 78%
“…We will then address an alternative hypothesis for the function of Broca's area based on these data. Auditory, phonological and word perception tasks Fiez et al (1996) Pseudo words-words (with instruction to remember list) þ (þPMC) Fiez et al (1996) Low frequency words-high frequency words þ þ Keller et al (2003) Comprehending tongue twister sentences-normal sentences (no covert production required) þ (þMFG, PMC) þ Schubotz and von Cramon (2002) Predict auditory pitch sequence; increase with sequence complexity þ (þPMC) Zatorre et al (1996) Detect /b/ in two syllable sequences-passive listening þ (þPMC) Zatorre et al (1996) Detect same final sound in two syllable sequences-passive listening þ Phonological and word production tasks Buckner et al (1995) Provide word from visual cue of first letters-fixation þ Buckner et al (1995) Verb generation-noun reading þ (þMFG) Gelfand and Bookheimer (2003) Manipulating syllable sequencesremembering syllable sequences þ (þMFG, PMC) Heim et al (2003) Phonological identification first sound of picture's name-semantic category decision þ (þMFG, PMC) þ (þMTG) Paulesu et al (1997) Generating words from initial lettergenerating words from semantic category þ Paus et al (1996) Increase with ate of whispering ba-lu (white noise mask against auditory feedback) þ Petersen et al (1989) Repeat word-hear/see it þ (þPMC) Syntactic/sentential perception manipulations Caplan et al (1999) Object-subject relative clauses þ Cooke et al (2002) Long antecedent-gap relations (particularly for object relatives)-short antecedent gap relations þ Fiebach et al (2001) Unambiguous object relative clauses with long delay to gap vs. with short delay to gap þ (Mid STG) Friederici et al (2003) Syntactic anomalies-correct sentences þ (þmid STG) Grossman et al (2002) Long antecenden gap-short antecendent gap distance interacts with subject vs. object relative clause þ Homae et al (2002) Sentences-phrases þ (þPMC) MTG Homae et al (2003) Sentences and phrases-non words þ (þMFG, PMC) þ (þMTG) Inui et al (1998) Center-embedded-left branching þ Just et al (1996) Center-embedded object relatives-conjoined verb phrase active þ þ Kuperberg et al (2003) Pragmatic violation > normal > agreement violation in sentences þ þ (þMTG) Meyer et al (2000)…”
Section: The Functions Of Broca's and Wernicke's Areasmentioning
confidence: 99%
“…Zatorre et al, 1996). Similarly, simply reading sentences containing words with similar sounds (tongue twisters) in order to answer a comprehension question does not require that they be produced; nevertheless, both Broca's and Wernicke's are more activated while reading tongue twisters than sentences containing words with less phonological similarity (Keller et al, 2003). Tasks which require overt or covert production show a similar pattern of co-activation.…”
Section: Production Versus Comprehensionmentioning
confidence: 99%
“…We used neurodegenerative disease as a model because it provides a wide distribution of neuropsychological scores and gray matter loss. We hypothesized that sentence comprehension will correlate with volumes in the left posterior temporal/inferior parietal region (Just et al, 1996;Keller et al, 2003), whereas vWM and comprehension of complex sentences will involve the left middle and inferior frontal gyri (Keller et al, 2001;Friederici et al, 2003).…”
Section: Introductionmentioning
confidence: 99%